Linguopragmatic Features Of Social Advertisements In English And Uzbekistan - Gafurova, Mutabar (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2025)
This article analyzes the linguo-pragmatic features of social advertisements created in English and Uzbek. Advertising language is a specific type of communication aimed at conveying a social idea, shaping behavior, and motivating positive action. The study examines the semiotic, linguistic, psychological, and stylistic features of advertising texts as well as their persuasive power and cross-cultural differences.